(untitled) (CIPEEX, 2026)
Introduction: The skin, the largest organ of the human body, plays essential roles such as protection, thermal regulation, and sensory perception. With aging, a reduction in elasticity occurs due to decreased collagen and elastin, resulting in wrinkles and fine lines. Nutrition is a key factor in skin health, and collagen supplementation may help minimize these effects, although results remain unclear in middle-aged women.Objective: To evaluate the impact of protein supplementation on skin appearance, elasticity, hydration, and oiliness, as well as on the levels of the growth factors VEGF and TGF-β.Methods: A total of 150 sedentary women aged 35–58 years were recruited and randomized into three groups: Verisol® Collagen 2.5 g/day, Peptech® Collagen 2.5 g/day, and Peptech® Collagen 10 g/day, for 3 months. Skin hydration, oiliness, and flexibility, as well as the number and depth of expression lines, were assessed, in addition to serum levels of Klotho, VEGF, and TGF-β. Statistical analysis was performed using GraphPad Prism 5.0, applying the Kolmogorov-Smirnov test and paired and unpaired Student’s t-test, with p<0.05 considered significant.Results: Supplementation with Verisol® Collagen promoted a significant increase in skin elasticity (p<0.04) and higher serum levels of TGF-β and VEGF. No changes were observed in hydration or oiliness.Conclusion: Verisol® Collagen showed positive effects on skin elasticity and on the modulation of biomarkers related to regeneration and skin function, representing a potential strategy for promoting skin health in middle-aged women.